Gagging Electoral Fraud in Nigeria: The Imperative of Electoral Reforms - Christiantus Ifeanyi Adebowale Oke; Harriet Omokiniovo Efanodor-Obeten (Khazanah Sosial, 2021)
Elections all over the world are the only recognized legitimate means of changing and constituting governments. In other democratic climes, citizens eagerly await elections with excitement, because it affords them the opportunity to appraise the scorecards of their elected representatives. However, preparing for elections in Nigeria is akin to getting set for a major warfare that requires humongous human and natural resources including the deployment of full military arsenal. Despite the unease this vital democratic practice puts the nation, elections are fraught with irregularities and malfeasances. The crux of this paper is to adumbrate what constitutes electoral fraud and proffer possible panaceas using the instruments of electoral reforms. The study utilizes secondary source of data and content analysis as its methodology and use qualitative approach. The paper argues that electoral malpractices manifest in diverse forms and are orchestrated by the political class to perpetuate themselves in office. It is also the opinion of this study that if there is a holistic electoral reform, most politicians that are currently occupying offices might not get valid chance of winning (re)elections, hence, their stiff opposition and resistance to the reforms. This paper recommends amongst others that the 9th National Assembly should as a matter of urgent national importance, timely debate, update and represent the Electoral (Amendment) Bill to the President for his assent. Furthermore, it is recommended that for free, fair and credible elections to take place, technology should be embraced and Electoral Offences Commission should be established to prosecute electoral fraudsters.